The concept of growth hacking : case study on Finnish companies - Kurikko, Katariina (2023)
The digitally revolutionized environment and availability of big data provide firms constantly arising new opportunities to deliver increased value for customers. However, this development has also challenged companies and marketers to adapt and transform their ideology and operating models to meet the current demands of empowered customers. One of the concepts that has emerged as a response to this need is growth hacking, a process that combines a data-driven mindset and multi-functional, customer-centric approach into marketing decision-making processes. This managerial-born concept originated from start-up world and thus, has received remarkable interest from practitioners and been implemented by larger businesses as well. Despite the prominent attention by practitioners, the academic research of the phenomenon is scant.